On Improving the Efficiency of the System of Competitions, Grants and Olympiads for Russian Students as an Element of Extracurricular Activities - A. V. Dozhdikov; O. V. Chicherina (Высшее образование в России)
The article addresses the issues regarding the formation of tools and methods to evaluate the achievements of Russian students in the olympiads, championships and competitions. These tools may improve the efficiency of higher education management system in the Russian Federation. The research methodology is connected with the empirical analysis of student survey data (N=2300) in several dimensions: in the context of periods of study and areas of training. The findings are supplemented with an analysis of the results of comparable studies and works of Russian authors. The article addresses the practical problems related to the need to compensate for the limitations on international academic mobility for Russian students, which are covered by the sanctions and other restrictions. The thesis of leveling the negative effects due to the quantitative and qualitative growth of the competition and olympiad movement in the Russian Federation is formulated. The authors have identified the main problems such as the low level of involvement of Russian students in extracurricular activities in comparison with their foreign colleagues; ineffective informational and organizational support of competitions and olympiads, directive, inflexible formation of the agenda and the lack of transparency in decision-making. The article formulates the proposals to improve the quality of extracurricular work at universities, to reform the system of competitions, grants and Olympiads for Russian students.